Sinergitas Kurikulum Madrasah Diniyah Takmiliyah dan Madrasah Formal di Pesantren - Samsul Arifin; Syuhud (Kitabaca : Journal of Islamic Studies, 2024)
Purpose – The fact that madrasah diniyah is a part of the network of Islamic educational institutions in Indonesia is thought to be detrimental to the institution's continued survival. Madrasah Diniyah, a school that emphasizes social functions to society so that they can continue to live and be civilized, is motivated by this challenge. Design/methodology/approach - This study is a sort of case study that employs a qualitative methodology. which emphasizes how Islamic boarding schools' curricula should be integrated into a complete curriculum synergy and uses research methods like interviews, observation, and documentation using valid cumulative data. Research limitations/implications – Combining a thorough curricular synergy with grass-roots theory to make it more adaptable for future madrasah. Findings/ Originality/Value – The Syarifuddin Islamic Boarding School's official curricula and madrasah diniyah were developed in concert. finished with the grass-roots approach. The only difference between the growth model and the one created by Beuchamp is that the latter does not employ the arena model..